Predictors of intention to stay for employees of casual dining restaurant in Klang Valley area - Mohamad Nashuki, Nasyira; Othman, Mohhidin; Ghazali, Hazrina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
Employees are an asset to an organisation where they could be the determinant behind organisational's success or failure in an industry. In this study, the relationship between perceived organisational support (POS), perceived supervisor support (PSS), and organisational commitment (OC) with employee's intention to stay with their current jobs were studied. For that purpose, 717 questionnaires were collected among casual dining restaurants employees in Klang Valley area and analyses Pearson correlation and multiple linear regression were run by using SPSS version 21. The results suggest that POS, PSS, and OC were positively correlated with employee's intention to stay with their current job. Furthermore, OC was also found to be the most influential factor in affecting employees' staying intention. The finding is hoped to have important implications where the management can formulate strategies to retain employees in restaurant industry in Malaysia.